The effect of iron and oxidizing flux addition on the fire assay of low grade pyritic refractory gold ores - Turan A.; Yucel O. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this study, experiments were conducted to understand the effects of different quantities of additional iron and oxidizing flux (Na2O2) on the direct fire assay of low grade pyritic refractory gold ores instead of performing any pre-treatment like roasting before fire assay. A portion of the pyritic ore was primarily roasted using a rotary kiln to remove sulphur content for the comparison of the results obtained from direct fire assay of the pyritic ore. Then, fire assay process was performed to the roasted ore and gold and silver content in the ore was determined. Unroasted ore specimens were fused by using fluxes and PbO, which accumulates the precious metals, with various quantities of iron. Correlation between the quantity of additional iron and the recovery of gold-silver were investigated. Various quantities of Na2O2, as an oxidizing flux, were added to the smelting charge with iron additions, from which the highest gold and silver recoveries were obtained from previous experiments. From the results, it was clear that the increase in additional iron and Na2O2 quantities was the reason for the increase in the recovered amounts of lead, gold and silver during the process.